New Concepts in Immunity to Neisseria Gonorrhoeae: Innate Responses and Suppression of Adaptive Immunity Favor the Pathogen, Not the Host - Liu, Yingru; Feinen, Brandon; Russell, Michael W. (Frontiers in Microbiology, 2011)
It is well known that gonorrhea can be acquired repeatedly with no apparent development of protective immunity arising from previous episodes of infection. Symptomatic infection is characterized by a purulent exudate, but the host response mechanisms are poorly understood. While the remarkable antigenic variability displayed by Neisseria gonorrhoeae and its capacity to inhibit complement activation allow it to evade destruction by the host’s immune defenses, we propose that it also has the capacity to avoid inducing specific immune responses. In a mouse model of vaginal gonococcal infection, N. gonorrhoeae elicits Th17-driven inflammatory- immune responses, which recruit innate defense mechanisms including an influx of neutrophils. Concomitantly, N. gonorrhoeae suppresses Th1- and Th2-dependent adaptive immunity, including specific antibody responses, through a mechanism involving TGF-β and regulatory T cells. Blockade of TGF-β alleviates the suppression of specific anti-gonococcal responses and allows Th1 and Th2 responses to emerge with the generation of immune memory and protective immunity. Genital tract tissues are naturally rich in TGF-β, which fosters an immunosuppressive environment that is important in reproduction. In exploiting this niche, N. gonorrhoeae exemplifies a well-adapted pathogen that proactively elicits from its host innate responses that it can survive and concomitantly suppresses adaptive immunity. Comprehension of these mechanisms of gonococcal pathogenesis should allow the development of novel approaches to therapy and facilitate the development of an effective vaccine.